The impact of work competency development program on public welfare and quality of life - Anthonius Anthonius; Nur Subeki; Mulyana Mulyana; Monica Agnes Sylvia (Faculty of Economics and Business, University of Muhammadiyah Malang, 2024)
Kartu Prakerja Programme is an end-to-end digital initiative aimed at enhancing the skills of the workforce through skilling, upskilling, and reskilling. Due to the COVID-19 pandemic, in its initial three years of implementation, the Kartu Prakerja Programme was executed under a semi-social assistance framework, providing training support and distributing social assistance. The objective of this research is to examine the public service innovation implemented by the Kartu Prakerja Programme and its impact on various aspects influencing community welfare and quality of life, particularly in West Java. This research is conducted using quantitative methods, employing questionnaire survey results from program recipients in West Java during 2020-2022 as the primary dataset. The study's findings demonstrate that the Kartu Prakerja Programme significantly contributes to enhancing the welfare and quality of life of individuals in Indonesia, including West Java. These contributions encompass the stimulation of employment and entrepreneurship, income growth, accelerated financial inclusion, enhanced competency, productivity, competitiveness, and promotion of lifelong education.